Kajian Umur Simpan Dan Nilai Gizi Barjaz Red Rice Tea Selama Penyimpanan Pada Suhu Ruang Dan Dingin - Lewi Gunadi, Tirza; Ari Yusasrini, Ni Luh; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This study aims to determine the effect of storage at room temperature and cold on shelf life and nutritional value of Barjaz Red Rice Tea and to determine the shelf life of Barjaz Red Rice Tea in storage at room temperature and cold. This study uses an experimental method with a quota sampling technique, in which the researcher has first determined the number of samples to be studied. Samples of Barjaz Red Rice Tea were taken from the Barjaz Tea production house located in Denpasar City, Bali Province. Barjaz Red Rice Tea parameters observed included total plate count, total sugar, anthocyanin content, antioxidant activity, and sensory assessment. The parameters studied were then analyzed using descriptive methods and the research data were presented in tabular form. The results showed that the shelf life and storage temperature had increase in the total plate number of Barjaz Red Rice Tea. Along with the long shelf life and high storage temperatures, the total plate number of Barjaz Red Rice Tea is getting higher. Based on total plate numbers, Barjaz Red Rice Tea that meets SNI 01-3143-1992 standards is Barjaz Red Rice Tea which is stored for zero days at room temperature and seven days at cold temperatures. Shelf life and storage temperature decrease the total sugar, anthocyanin levels, and antioxidant activity of Barjaz Red Rice Tea. Along with the long shelf life and high storage temperature, the total sugar, anthocyanin content, and antioxidant activity of Barjaz Red Rice Tea will decrease. The total sugar samples of Barjaz Red Rice Tea, both stored at room temperature and cold temperatures, still meet the standards set by SNI 01-3143-1992. Storage temperature influenced panelists' assessment of the sensory evaluation of color, aroma, taste and overall assessment of Barjaz Red Rice Tea. The criteria for Barjaz Red Rice Tea that are still suitable for consumption and favored by panelists are those that have a dark red color, a distinctive aroma of red rice tea, and a slightly sweet taste.